EFFECTS OF COMPETENCE, ETHICAL BEHAVIOR, AND WORK MOTIVATION ON PREVENTION OF FINANCIAL REPORTING FRAUD: WHISTLEBLOWING SYSTEM AS A MODERATOR - Ina Mutmainah (UNIB Press, 2022)
The present study aims to examine the effect of human resource competence, ethical behavior, and work motivation on the prevention of financial reporting fraud moderated by whistleblowing systems. Primary data were garnered from banks in Pekalongan, Central Java, Indonesia. This study employed a moderation regression analysis with an interaction testing. Study findings reveal that human resource competence and work motivation give a significant effect on the prevention of financial reporting fraud, while ethical behavior had no significant effect on the prevention of financial reporting fraud. In addition, whistleblowing systems strengthened both the negative effect of human resource competence on the prevention of financial reporting fraud and the positive effect of ethical behavior on the prevention of financial reporting fraud. Nonetheless, the whistleblowing system did not moderate work motivation toward the prevention of financial reporting fraud. The control variable, i.e., reward and punishment, showed a significant impact on the prevention of financial reporting fraud. The study concludes with some empirical evidence for how banking management fosters the whistleblowing system to prevent financial reporting fraud.